Beyond investigation-relevant information: a content analysis of police questioning. (25th May 2021) - Launay, Céline; Py, Jacques; Brunel, Maïté; Demarchi, Samuel
ABSTRACT: There are two primary investigative interview objectives: gathering information to determine what happened and who did it and assessing the witness's reliability. The present study examined to what extent investigative interviewers gather investigation-relevant information (IRI) compared to interviewee details (ID) to assess witness reliability. As part of a training course, 42 police officers participated as interviewers and mock witnesses by viewing a crime video. The interviews were recorded and rated for question type and question content through thematic analyses. IRI questions accounted for 78% of the questions asked, while ID questions accounted for 22% of the questions asked. The police officers assessed the way witnesses perceived this information and the attendant meta-processes and used more inappropriate questions than appropriate questions. These results help to elucidate the objectives of police interviews that should be considered when evaluating witness performances in laboratory settings and when developing effective interviewing protocols.